Disaggregating the components of a monthly water resources system model to daily values for use with a water quality model. (June 2016) - Hughes, D.A.; Slaughter, A.R.
Abstract: A model designed to disaggregate the water balance components of a monthly water resources system model to daily time series is presented. The objective of the model is to add value to existing monthly model setups and to provide daily water balance data for a water quality model. The model components include the disaggregation of incremental catchment flows, run-of-river and reservoir abstractions, reservoir releases for users and environmental flow requirements and reservoir spills. While previous studies have demonstrated that the main incremental catchment flow component is fit-for-purpose, the overall model is difficult to validate due to the impacts of imperfect monthly model simulations and the variability in operational practises compared with operational design procedures that form the basis of the model algorithm. Despite these reservations, the model is considered to provide a pragmatic, but useful approach to disaggregating monthly water balance simulations for use within a daily water quality model. Highlights: A pragmatic model is presented to disaggregate monthly water balance components to daily time series. The main objective was to provide a link between monthly systems models and a daily water quality model. While there are inevitable uncertainties in the structure of the model, it is 'fit-for-purpose'.